14.8k views
5 votes
Whats the answer for -(3x-9) use the distributive property to simplify

User SlashmanX
by
6.3k points

1 Answer

2 votes

Answer: x=3

Step-by-step explanation: you can rewrite -(3x-9) as -1*(3x-9). as the negative sign is the same as -1. Now if you distribute you get -3x+9. then set this equation equal to zero and subtract 9 from both sides and you'll get -3x=-9. next divide both sides by -3 and you should get the answer x=3.

-(3x-9)

-1*(3x-9)

-3x-9=0

-3x=-9

x=3

User Obelix
by
5.9k points